AUA Quality Improvement Summit 2014: Conference Proceedings on Infectious Complications of Transrectal Prostate Needle Biopsy. Issue 4 (July 2015) - Averch, Timothy; Tessier, Christopher; Clemens, Quentin J.; Franks, Michael; Gonzalez, Christopher; Jones, Stephen J.; Kapoor, Deepak A.; Lightner, Deborah J.; Liss, Michael; Montie, James; Watson, Richard A.; Wolf, Stuart J.
Abstract : Introduction: : The AUA Quality Improvement Summit is a continuing AUA effort to provide education around issues related to quality improvement and patient safety. Due to the rapidly increasing rates of hospitalization following prostate needle biopsy, Infectious Complications of Transrectal Prostate Needle Biopsy was selected as the inaugural topic. Methods: : The information is largely unpublished data provided by the presenting physicians. Infection rates are predominantly self‐reported with protocols specified by the physicians' home institutions. Beyond the identified speakers, the open forum of this summit allowed for input from a majority of the participants. Results: : Current hospitalization rates for transrectal prostate needle biopsy infections vary widely from 0.5% to 6%. Antibiotic resistance of coliform organisms appears to be a major risk of these infectious complications. Prophylactic protocols also vary widely among the represented institutions. Antibiotic resistance profiles showed extreme regional variation and, as such, a prophylactic antibiotic protocol should be based on the current local antibiogram in order to reduce infection rates. Opinions vary in relation to the specific antibiotics appropriate for an augmented antibiotic prophylaxis, in the use of rectal swab and prebiopsy enema, and povidone‐iodine preparation of the rectal vault. Standardization of the transrectal antibiotic prophylaxis across practices has been proven to reduce the infectious complications rates. Conclusions: : Urologists should monitor the prostate biopsy infection rates of the practice and consult the current local antibiogram. Physicians should query patients to assess whether they are at high risk for resistant organisms. If so, prophylactic protocols might be intensified.